Scintigraphic study of the splenic circulation in rats - Rodrigues,Fábio Gontijo (2014)
Objective: To evaluate the splenic parenchymal blood distribution through scintigraphic study.Methods: Thirty Wistar rats were randomly divided into six groups (n = 5). Group 1 (spleen - 30 minutes) and Group 2 (spleen - 90 minutes) underwent laparotomy with direction of blood flow to the spleen by ligature of the aorta near the iliac bifurcation and splanchnic vessels, keeping blood flow only in the splenic artery; Group 3 (spleen and stomach - 30 minutes) and Group 4 (spleen and stomach - 90 minutes) underwent laparotomy with direction of blood flow to the spleen and stomach by ligature of the aorta near the iliac bifurcation and splanchnic vessels, maintaining the flow through the splenic, gastric and splenogastric vessels; Group 5 (control - 30 minutes) and Group 6 (control - 90 minutes) underwent laparotomy and ligation of the aorta near the iliac bifurcation, keeping the flow to the abdominal organs. After arterial ligation, the animals received an injection of 0.2 ml of sodium pertechnetate in the aorta. Scintigraphic images were taken and the animals had their spleens removed for radioactivity counting with an automatic counter device.Results: There was no difference in the amounts of radiation from the spleen between groups, indicating retention of the radioisotope by the spleen, even after the period of 90 minutes.Conclusion: The blood flow through the spleen is not continuous. The blood diffuses through the splenic parenchyma and its venous drainage is slow, not following a predictable sequence.